Microstructural, mechanical, and thermal characterization of constitutive layers in copper-steel functionally graded material manufactured via laser directed energy deposition - Tobia Romano; Marawan Abdelwahed; Virgínia Bertolo; Tommaso Cecotti; Samuel Skhosane; Gautham Mahadevan; Vera Popovich; Marcel Hermans; Mohamed A. Taha; Sisa Pityana; Maurizio Vedani (Materials & Design, 2025)
Copper-steel functionally graded materials combine the thermal conductivity of copper with the mechanical strength of steel. This study examines the microstructural, mechanical, and thermophysical properties of the constitutive layers of copper-4130 steel functionally graded material fabricated via laser directed energy deposition, considering four intermediate compositions: 100% 4130, 75% 4130 – 25% Cu, 50% 4130 – 50% Cu, and 25% 4130 – 75% Cu. It was observed that the amount of Cu-rich terminal liquid governs crack formation and backfilling during solidification, while Cu-Fe liquid phase separation and Marangoni convection within the melt pool generate macrostructures composed of alternating Cu- and Fe-rich phases. Increasing Cu content progressively enhances thermal diffusivity due to the formation of interconnected copper regions. The application of quenching and tempering treatments induced softening of Cu-containing samples due to Cu recrystallization and diffusion from supersaturated Fe-rich phases. Although solidification cracking was only observed in 75% 4130–25% individual samples, the analysis of a complete multilayer structure revealed that interlayer mixing causes local compositional variations, extending cracking susceptibility beyond this region. These findings provide insights into the key factors governing laser directed energy deposition of copper-steel functionally graded materials, supporting process optimization and predictive model development to enhance manufacturability.